Kedudukan Hukum Smart Contract dalam Sistem Perjanjian Menurut Hukum Perdata Indonesia - Ardina Widya Hapsari; Aturkian Laia (INDO PUBLISHING, 2026)
The development of blockchain technology has introduced smart contracts as self-executing agreements that operate automatically through computer code without requiring human intervention or intermediaries. This study aims to examine the legal status, validity, binding force, and regulatory challenges of smart contracts within the Indonesian civil law system. The research employs a normative juridical method using statutory and conceptual approaches, analyzed through a prescriptive-qualitative method. The findings indicate that smart contracts are capable of fulfilling the legal requirements for a valid agreement under Article 1320 of the Indonesian Civil Code and are recognized as electronic contracts under the Electronic Information and Transactions Law. However, their immutable, automated, and decentralized characteristics create legal challenges concerning parties' legal capacity, contract annulment, force majeure, and liability arising from code errors. Therefore, a sui generis regulatory framework is required to harmonize the technical characteristics of smart contracts with the principles of Indonesian contract law.